Implementasi Manajemen Laba pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Ditya Permatasari (Jurnal Ekonomi Akuntansi dan Manajemen, 2017)
This study aims to determine the real earnings management are proxied by cash flow from operation, production cost, discretionary expenses and combination real earnings management. This study uses the prospect theory. Research samples were 93 manufacturing companies listed in Indonesia Stock Exchange during 2012-2014. Grouping the sample companies were allegedly identified and unidentified perform earnings management by using the distribution of EPS. EPS distribution based on reference point 5%, by comparing profit in this year and profit in the last year. The result of this study explained that manufacturing companies in Indonesia do real earnings management by increasing operating cash flow operation, increasing production cost and decreasing discretionary expenses to avoid decreasing profit. All proxies of the real earnings management support the hypothesis in this study, except combination real earnings management. Firm size and leverage don’t affect the real earnings management in manufacturing companies in Indonesia. Keywords: Real Earnings Management, Proxies of Earnings Management Laba Riil, Prospect Theory, Distribution of EPS.